2019
DOI: 10.1038/s41522-019-0094-5
|View full text |Cite|
|
Sign up to set email alerts
|

Candida albicans biofilm development is governed by cooperative attachment and adhesion maintenance proteins

Abstract: The opportunistic fungal pathogen Candida albicans is capable of adhering to the oral mucosa despite forces created by salivary flow. Although many fungal adhesion proteins have been identified, less is known about the temporal development of cell adhesion and biofilm growth in a flow environment. In this study, we use a flow system with real-time imaging of C. albicans cells as they adhere and grow. Rates of cell attachment and dispersion of C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 33 publications
3
62
1
1
Order By: Relevance
“…In Salmonella, biofilm-associated protein, BapA, is an important structural component for biofilm formation, and calcium was found to be important for proper protein folding (Guttula et al, 2019). In addition, biofilm-associated surface proteins are important for the maintenance of biofilm (McCall et al, 2019). Fourth, calcium can function as a signal and induce the expression of genes involved in different pathways to mediate biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In Salmonella, biofilm-associated protein, BapA, is an important structural component for biofilm formation, and calcium was found to be important for proper protein folding (Guttula et al, 2019). In addition, biofilm-associated surface proteins are important for the maintenance of biofilm (McCall et al, 2019). Fourth, calcium can function as a signal and induce the expression of genes involved in different pathways to mediate biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the YWP1 gene was upregulated with SM-F2 treatment. YWP1 (Yeast Wall protein 1) is an anchored glycoprotein of the cell wall present only in the yeast form, absent in filamentous form and chlamydospores (Granger, 2012;McCall et al, 2019). Therefore, these results suggest that the activity of SM-F2 against filamentation observed in the microscopic analysis can be associated with the level of transcription in C. albicans cells that leads to retention in the yeast state.…”
Section: Discussionmentioning
confidence: 78%
“…The Dongari-Bagtzoglou group previously showed that the presence of oral streptococci increases the ability of C. albicans to invade organotypic models of oral mucosa ( 9 ) and that Streptococcus oralis can activate C. albicans EFG1 gene expression (a key inducer of hyphae and microcolonies) that increases polymicrobial biofilm ( 52 ). In addition, coinfections of S. oralis and C. albicans increase mucosal fungal invasion ( 53 ), and coculture of C. albicans with S. gordonii induces the expression of fungal filamentation genes and hyphal adhesins, including Als1, Hyr1, and Eap1 ( 11 ), some of which we showed are important for microcolony adhesion ( 54 ). However, we found that S. gordonii supernatants induced a dual phenotype, with the majority of C. albicans microcolonies becoming enlarged and detached from an underlying epithelium, while some microcolonies (30%) had less biomass but were highly invasive.…”
Section: Discussionmentioning
confidence: 92%